(untitled) (Medico Legal Update, 2020)
The research aims to know the impact of using the strategies of cognitive perception on the achievement and practical performance of physiology, and to achieve the goal of the research under the formulation of zero hypotheses: There is no statistically significant difference at the level of (05.0) between the average grades of students in the achievement of students of the three groups of physiology. There is no statistically significant difference at the level of (05.0) between the average grades of students in the practical performance of the students of the three groups of physiology. The research community consisted of the students of the first stage in the Technical Institute. The sample was randomly tested as it reached 45 students. The equivalence between the research groups was confirmed through the following variables: (Age, Intelligence). As for practical achievement, (15) objective test items were drafted covering the subject, and to ensure the validity of the test was presented to a number of experts specialized in education and teaching methods, and the validity and consistency of the discrimination factor and the difficulty factor and the effectiveness of alternatives to the test were calculated.